Effectiveness of Law Enforcement of Article 23 of Law No. 12 of 2022 on the Prohibition of the Implementation of Restorative Justice in Cases of Sexual Violence - Domaking, Lusiana Dau; Subrakah, Ibnu; Ma'sumah, Mufidatul (Riviera Publishing, 2025)
This study analyzes the effectiveness of law enforcement against the prohibition on the application of restorative justice in cases of sexual violence as specified in Article 23 of Law No. 12 of 2022. This law prohibits the resolution of sexual violence cases through out-of-court channels for adult perpetrators, but practice in the field shows that the restorative justice mechanism is still often applied by law enforcement officers using the Chief of Police Regulation No. 8 of 2021 as the legal basis. The study was conducted at the Malang City Police and the Malang City Social Service P3AP2KB, which revealed obstacles such as social pressure, lack of public education, and the reluctance of victims to continue cases to the legal route. The results of the study show that the application of Article 23 has not been fully effective in protecting victims' rights and preventing re-victimization. This study recommends harmonization of regulations between Law No. 12 of 2022 concerning Criminal Acts and Perpol no. 8 of 2021, increasing public education, and strengthening legal and psychological assistance for victims.